2017
DOI: 10.1021/acs.jpcc.7b00688
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Design and Fabrication of SERS–SEF Multifunctional Nanoparticles for Nanoprobe Applications: Morphology-Dependent SERS Phenomena

Abstract: Dual-mode surface-enhanced Raman scattering (SERS)–surface-enhanced fluorescence (SEF) composite nanoparticles have been developed for possible use as oil reservoir tracers. These composite nanoparticles are composed of metal Ag nanostructured cores, specific dye molecules, and a SiO2 shell coating. Herein, we show that the embedded dye molecules are detectable by both Raman and fluorescence spectroscopies and yield dramatically enhanced detectability due to strong SERS–SEF phenomena with limits of detection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Finally, this work also considers the effect of different ions in the fluids, which the specific motivation stems from recent efforts to deploy nanomaterials for subsurface oil reservoir applications. To the best of our knowledge, this is the first study showing the interaction of nanomaterials on different calcite surface defects, mediated by specific ions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this work also considers the effect of different ions in the fluids, which the specific motivation stems from recent efforts to deploy nanomaterials for subsurface oil reservoir applications. To the best of our knowledge, this is the first study showing the interaction of nanomaterials on different calcite surface defects, mediated by specific ions.…”
Section: Introductionmentioning
confidence: 99%
“…The unique properties of nanomaterials have the potential to achieve much higher performance in the above mentioned applications. For example, the ultra-sensitive optical properties 12,13 (e.g. persistent luminescence and surface-enhanced Raman scattering) may be used in reservoir interwell tracers for improved waterflood recovery optimization 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…The maximal enhancement factor of Raman and fluorescence was 10 6 and 9-fold, respectively. In Change et al’s study [14], silver nanoparticles demonstrate both SERS and SEF properties. They have found that metallic particles’ aggregation status together with the interval between metal structure and emitters strongly influence the enhancement ratio.…”
Section: Introductionmentioning
confidence: 99%